La terminación de la relación laboral por incapacidad provenientes por accidente de tránsito - Pino Tomalá, Jean Pierre (2022)
The employment relationship is considered the existing legal bond between the worker and the worker, the same one that is established by means of a contract who are obliged to comply with what is stipulated in the clauses and the existing legal regulations in the country in which At present, every labor relationship is governed by a labor contract that links both figures, this serves to regulate working conditions, always based on the fact that the clauses of the contract are in accordance with the current law, the worker within labor relations, has some fundamental tasks for the company to function properly in principle this is subject to rights as well as obligations. The objective of this study is to analyze the legal provisions of the Labor Code that support the termination of the employment relationship due to disability resulting from a traffic accident, in order to improve the application of the law and guarantee the rights of the parties involved, in the presence of contingencies called In Itinere occupational traffic accidents today represent a problem of high social and economic impact and are one of the greatest concerns in modern societies there are some premises that allow identifying an accident in itinere however, it should be noted that this notion is being broadened by a jurisprudence that is valuing, among other things, the need to safeguard the conciliation between work and family life.......